THE INFLUENCE OF STUDENT BACKGROUND CHARACTERISTICS ON PROFICIENCY IN ENGLISH AS A FOREIGN LANGUAGE: INDONESIAN CONTEXT - Ratna Rintaningrum; Carol Aldous; John P Keeves (Institut Teknologi Sepuluh Nopember, 2017)
In order to explain differences in English proficiency level, one needs to consider a number of factors frequently considered important at a variety of level of education systems. Among the factors that operate to influence English Foreign Language Proficiency are those associated with the student background variables. This study identifies the student level factors that influence English Foreign Language Proficiency. It is expected that this study can contribute to the development of a theory of foreign language learning that applies to students studying the English language at other universities in Indonesia and South-East Asia. This study involves the employment of an exploratory approach for the examination of the relationships between variables operating at the student level. Data are analyzed using Partial Least Squares Path Analysis (PLSPATH) to identify in an exploratory way the variables that have significant direct and indirect effects on English Foreign Language Proficiency. The study shows that a number of student background characteristics such as sex of student (GENDER), socio-economic of student (SES), Faculty of Instruction (FACULTY), score of English 1 (ENGLISH_1) and semester in which students enrol in English 2 (SEMESTER) have only direct effects on English Language Proficiency, while student prior achievement (PRIOR) has both direct and indirect effects on English Foreign Language Proficiency